Extending supply side statistics for the tourism sector: A new approach based on linked-administrative data - Delaney, Jillian; MacFeely, Steve (Statistical and Social Inquiry Society of Ireland, 2014)
This paper presents a new approach to measuring and understanding the activities of the tourism industries in Ireland. Using structural business statistics and administrative registers a new set of static and dynamic supply-side indicators are developed at both national and sub-national level. These indicators not only complement and expand the suite of tourism indicators already available but also offer a practical approach to filling a gap in the UNWTO – 2008 International Recommendations on Tourism Statistics.
Keywords: registers; tourism dependency ratios; International Recommendations on Tourism Statistics; 314.15